Diaries as support for memories: : Quarto de despejo, by Carolina Maria de Jesus (1960), and Diário do fim do mundo, by Maria Nilda de Carvalho Mota (2020) (Comunicação & Inovação, 2022)
We seek to understand, through the textual analysis of two diaries of black women, who lived in slums, Quarto de despejo (1960), by Carolina Maria de Jesus, and Diário do fim do mundo (2020), by Maria Nilda de Carvalho Mota, the representations about police actions in the periphery of São Paulo. We analyzed the sociopolitical context, the diary as a support of memories and truths and as a literary genre. For Carolina de Jesus the police ensured her survival, but for Maria Mota it was the opposite. We rely on theorists about diary writing and violence.
Keywords: Memory; Diaries; Police violence